Psychological treatment for people with musculoskeletal pain 1 - Pincus, Tamar (Henry Stewart Talks, 2015)
Psychological processes/factors associated with transition to chronic pain, Depression in the context of pain, Illness perception, Fear avoidance, Effective reassurance, Psychological interventions for people with LBP